Arahan Konservasi Pada Zonasi Daerah Imbuhan Mata Air di Dusun Plesedan, Desa Srimulyo, Kecamatan Piyungan Kabupaten Bantul, D.I Yogyakarta - Dika Maknalia Prastiwi; Eni Muryani; Andi Renata Ade Yudono (Jurusan Teknik Lingkungan, FTM, Universitas Pembangunan Nasional “Veteran” Yogyakarta, 2019)
Determination of springs replenishment area based on the criteria of the Minister of Public Works Regulation No. 02 of 2013 is the key in proper and efficient springs management engineering. The recharge area that is not managed properly contributes to influencing the flow of the spring. The absence of management of catchment areas causes a decrease in the number of springs. The area of interest of the spring studied was classified based on rainfall, soil texture, land use, and slope. The aim of this study is to determine the criteria for spring water supply areas based on the scoring of Ministerial Regulation No.2 of 2013. The research sites were in Plesedan Village, Srimulyo Sub District, Piyungan District, Bantul Regency, D.I Yogyakarta Province. Determining the location of the springs recharge area based on Minister of Energy and Mineral Resources Regulation No. 13 of 2009, which is evaluated using the Minister of Public Works Regulation No. 02 of 2013. The method used includes survey and mapping methods to determine the condition of existing spring springs, as well as mathematical analysis methods for calculating the scoring of spring springs. The Grab sampling method was used to determine the texture of the soil at the study site. The results of the study found that the zoning of the springs area was divided into two categories. The bad category area has a score of 4-12 and the good category has a score of <12-20. The direction for managing the spring extension area is then adjusted to the zoning of the recharge area at the research location. Management of bad recharge by using drainage channel, and for good recharge areas vegetation method approaches are carried out. Keywords: Recharge Area, Springs, Conservation of Recharge Area, Geospatial Analysis.